TINJAUAN YURIDIS EKSEKUSI PIDANA MATI DI INDONESIA - Soge, Paulinus (Faculty of Law, Universitas Sebelas Maret, 2012)
AbstractFrom the juridical perspective, execution of death penalty in Indonesia is carried out by firing to death based on Law No. 2 Pnps 1964. Such a method was stressed again by Constitution Court in its sententce No. 21/PUU-VI/2008 which refused to change method of execution with the other one that would not be a torture for the condemned as requested by those condemned of death penalty in Bali bomb case, Amrosi and his friends. The Contitution Court considered that execution of death penalty based on this law has the risk of unaccuracy which can cause pain, but it is not a torture meant by Article 28I of the 1945 Constitu- tion. AbstrakEksekusi pidana mati di Indonesia ditinjau dari perspektif yuridis dilaksanakan dengan ditembak sampai mati berdasarkan UU No. 2 Pnps Tahun 1964. Hal ini ditegaskan kembali oleh Mahkamah Konstitusi (MK) dalam putusan No. 21/PUU-VI/2008 yang menolak mengganti cara eksekusi pidana mati dengan cara lain yang bersifat tidak menyiksa terpidana sebagaimana dimohon oleh para terpidana mati kasus bom Bali, Amrozi dan teman-temannya. MK berpendapat bahwa eksekusi pidana mati berdasarkan Undang Undang ini mengandung risiko terjadinya ketidaktepatan dalam pelaksanaan yang menimbulkan rasa sakit, namun hal itu bukan merupakan penyiksaan sebagaimana dimaksud Pasal 28I UUD 1945.